KOMODIFIKASI SONGKET SILUNGKANG DALAM PENGEMBANGAN PARIWISATA DI KOTA SAWAHLUNTO - seprisyam seprisyam; Hasanuddin Hasanuddin; Pramono Pramono (JURNAL ILMU BUDAYA, 2021)
This study aims to explain the commodification of Songket Silungkang in the tourism development of Sawahlunto Town. This research is descriptive research with a qualitative approach. Data were obtained from field observations, recorded interviews, and documentary studies of Songket Silungkang. The data obtained were processed using ethnographic methods. The results of this study found that the commodification of Songket Silungkang occurs from the production process to consumption. Factors that influence the commodification of Songket Silungkang are changes in the social structure of society, education level, media and globalization, tourism, and creative industries. SISCA implemented by the Town Government of Sawahlunto is a step to promote tourism. The positive impact of the commodification of Songket Silungkang adds to the value of Songket and improves the economy of the community, while the negative impact of the commodification of Songket Silungkang loses the meaning of the Songket Silungkang motif.